Net-public sphere research - Dahlberg, Lincoln (Javnost (Ljubljana), 2004)
In recent years much has been said about the possibility of the Internet facilitating and extending the public sphere of informal rational-critical communication between private affairs and official decision making. However, the abundant speculation has not yet been matched by extensive empirical research. Ongoing theoretical debate about the validity and content of the public sphere conception makes empirical evaluation difficult, as does the Internetćs constitution through a vast and dynamic array of human interactions, cultural contexts, and social institutions. Despite these difficulties, a number of pioneering studies have attempted to investigate theNet-public sphere relation. In this paper I offer a critical reflection upon some of these early studies, a reflection that explores three reoccurringmethodological problems and their possible solutions, with the aim of providing strategies for developing more meaningful Net-public sphere research. These problems involve: developing a normative conception of the public sphere suitable for critical analysis; improving the transition betweentheory and empirical evaluation; and adequately explaining and extending findings. My suggested solutions include the specification of publicsphere criteria from Habermas' theory of communicative rationality; the identification of a variety of case sensitive indicators that can facilitate the transition between criteria and practice; and the suggestion that explanation and extension of findings be undertaken by way of comparative case study research.
Keywords: javnost; javna sfera; communication; komuniciranje; množične komunikacije; odločanje; teorija komunikacij; informacijska tehnologija; information technology; računalniška omrežja